Activity-Dependent Regulation of the Proapoptotic BH3-Only Gene egl-1 in a Living Neuron Pair in Caenorhabditis elegans. Issue 11 (1st November 2019) - Cohn, Jesse; Dwivedi, Vivek; Valperga, Giulio; Zarate, Nicole; de Bono, Mario; Horvitz, H Robert; Pierce, Jonathan T
Abstract: The BH3-only family of proteins is key for initiating apoptosis in a variety of contexts, and may also contribute to non-apoptotic cellular processes. Historically, the nematode Caenorhabditis elegans has provided a powerful system for studying and identifying conserved regulators of BH3-only proteins. In C. elegans, the BH3-only protein egl-1 is expressed during development to cell-autonomously trigger most developmental cell deaths. Here we provide evidence that egl-1 is also transcribed after development in the sensory neuron pair URX without inducing apoptosis. We used genetic screening and epistasis analysis to determine that its transcription is regulated in URX by neuronal activity and/or in parallel by orthologs of Protein Kinase G and the Salt-Inducible Kinase family. Because several BH3-only family proteins are also expressed in the adult nervous system of mammals, we suggest that studying egl-1 expression in URX may shed light on mechanisms that regulate conserved family members in higher organisms.